Family business internationalization : The process and factors influencing the internationalization decision - Semanová, Martina (2022)
Family business internationalization is an important research topic due to the significance of small and medium-sized family firms in the global economy. Similarly, the research field provides limited and inconclusive conclusions on how family firms internationalize, henceforth this master's thesis aims to explore the factors that influence family firms' decision to internationalize as well as the process of their foreign expansion.